The effect of ionizing radiation through cardiac stereotactic body radiation therapy on myocardial tissue for refractory ventricular arrhythmias: A review - Whitaker, John; Zei, Paul C.; Ahmad, Shahreen; Niederer, Steven; O'Neill, Mark; Rinaldi, Christopher A. (Frontiers in Cardiovascular Medicine, 2022)
Cardiac stereotactic body radiation therapy (cSBRT) is a non-invasive treatment modality that has been recently reported as an effective treatment for ventricular arrhythmias refractory to medical therapy and catheter ablation. The approach leverages tools developed and refined in radiation oncology, where experience has been accumulated in the treatment of a wide variety of malignant conditions. However, important differences exist between rapidly dividing malignant tumor cells and fully differentiated myocytes in pathologically remodeled ventricular myocardium, which represent the respective radiation targets. Despite its initial success, little is known about the radiobiology of the anti-arrhythmic effect cSBRT. Pre-clinical data indicates a late fibrotic effect of that appears between 3 and 4 months following cSBRT, which may result in conduction slowing and block. However, there is clear clinical evidence of an anti-arrhythmic effect of cSBRT that precedes the appearance of radiation induced fibrosis for which the mechanism is unclear. In addition, the data to date suggests that even the late anti-arrhythmic effect of cSBRT is not fully attributable to radiation.-induced fibrosis. Pre-clinical data has identified upregulation of proteins expected to result in both increased cell-to-cell coupling and excitability in the early post cSBRT period and demonstrated an associated increase in myocardial conduction velocity. These observations indicate a complex response to radiotherapy and highlight the lack of clarity regarding the different stages of the anti-arrhythmic mechanism of cSBRT. It may be speculated that in the future cSBRT therapy could be planned to deliver both early and late radiation effects titrated to optimize the combined anti-arrhythmic efficacy of the treatment. In addition to these outstanding mechanistic questions, the optimal patient selection, radiation modality, radiation dose and treatment planning strategy are currently being investigated. In this review, we consider the structural and functional effect of radiation on myocardium and the possible anti-arrhythmic mechanisms of cSBRT. Review of the published data highlights the exciting prospects for the development of knowledge and understanding in this area in which so many outstanding questions exist.